WITHDRAWN: Behavioral abnormalities in young female mice following administration of aluminum adjuvants and the human papillomavirus (HPV) vaccine Gardasil (2016)
This article has been withdrawn at the request of the Editor-in-Chief due to serious concerns regarding the scientific soundness of the article. Review by the Editor-in-Chief and evaluation by outside experts, confirmed that the methodology is seriously flawed, and the claims that the article makes are unjustified. As an international peer-reviewed journal we believe it is our duty to withdraw the article from further circulation, and to notify the community of this issue. The full Elsevier Policy on Article Withdrawal can be found at http://www.elsevier.com/locate/withdrawalpolicy.